2016
DOI: 10.2337/db16-0761
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Overexpression Induces Glucagon Resistance and Protects Animals From Chemically Induced Diabetes

Abstract: Heparanase, a protein with enzymatic and nonenzymatic properties, contributes toward disease progression and prevention. In the current study, a fortuitous observation in transgenic mice globally overexpressing heparanase (hep-tg) was the discovery of improved glucose homeostasis. We examined the mechanisms that contribute toward this improved glucose metabolism. Heparanase overexpression was associated with enhanced glucose-stimulated insulin secretion and hyperglucagonemia, in addition to changes in islet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Opposite to the hyperglycaemia phenotypes observed in heparin-treated BL6 mice, we found that long-term systemic treatment of heparinase, a heparin cleavaging enzyme, significantly decreased blood glucose in diabetic db/db mice, but not in normal chow-fed BL6 mice. These findings are reminiscent of those observed in heparanase overexpression mice, which have decreased heparan sulphate, 22 with decreased blood glucose levels in STZ-induced diabetic condition, but not in normal physiological condition. This may be attributed to the fact that low levels of heparin are present in the blood under normal physiological condition, while hyperheparinemia is associated with diabetic conditions.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Opposite to the hyperglycaemia phenotypes observed in heparin-treated BL6 mice, we found that long-term systemic treatment of heparinase, a heparin cleavaging enzyme, significantly decreased blood glucose in diabetic db/db mice, but not in normal chow-fed BL6 mice. These findings are reminiscent of those observed in heparanase overexpression mice, which have decreased heparan sulphate, 22 with decreased blood glucose levels in STZ-induced diabetic condition, but not in normal physiological condition. This may be attributed to the fact that low levels of heparin are present in the blood under normal physiological condition, while hyperheparinemia is associated with diabetic conditions.…”
Section: Discussionsupporting
confidence: 64%
“…These observations are consistent with indirect evidence regarding another member of the GAG family, heparan sulphate, which shares a very similar structure with heparin. Heparanase, the catalytic enzyme of heparin sulphate, has been shown to effectively alleviate genetic and chemical‐induced T1DM in mice 21,22 . Additionally, we tested the blood glucose levels after chronic treatment of two other heparin derivatives, desulphated heparin (DSH with lower anticoagulant activity) and low‐molecular‐weight heparin (LMWH with higher anticoagulant activity).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In type-2 diabetes mellitus patients, urine HPSE was shown to correlate with high blood glucose levels, indicating glucose-mediated HPSE expression and secretion, with follow up in vitro studies showing insulin-mediated HPSE secretion by human embryonic kidney cells in culture [305]. The interesting observation of HPSE improving glucose metabolism was made in a study of transgenic HPSE-overexpressing mice, with significant changes in pancreatic islet cell composition, structure, gene expression and the overall protective effect from streptozotocin-induced diabetes [306].…”
Section: Reprogramming Energy Metabolism: An Emerging Hallmarkmentioning
confidence: 97%
“…97 These findings are in agreement with those from previous studies that established a protective function of heparanase in the acutely diabetic heart, in which it conferred cardiomyocyte resistance to oxidative stress and apoptosis by provoking changes in gene expression. 98 In line with these findings, unfolding protein response and autophagy inhibitors have been reported to reduce the protective effects of heparanase overexpression during I/R, suggesting that heparanase promotes cell survival by providing protection against cellular stresses, and consequently prevents glycocalyx detachment. 97 The observed unfolding protein response activation in I/R Hpa-Tg mice was adaptive and not apoptotic, mediated by the activation of activating transcription factor 6a and, when combined with mammalian target of rapamycin inhibition, induced autophagy.…”
Section: Heparan Sulfate and Heparanasementioning
confidence: 55%